2017
DOI: 10.1152/ajpendo.00329.2016
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitizer prevents and ameliorates experimental type 1 diabetes

Abstract: Insulin-dependent type-1 diabetes (T1D) is driven by autoimmune β-cell failure, whereas systemic resistance to insulin is considered the hallmark of insulin-independent type-2 diabetes (T2D). In contrast to this canonical dichotomy, insulin resistance appears to precede the overt diabetic stage of T1D and predict its progression, implying that insulin sensitizers may change the course of T1D. However, previous attempts to ameliorate T1D in animal models or patients by insulin sensitizers have largely failed. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Studies on insulin resistance in type 2 diabetes have suggested that the dysregulated insulin pathway is involved in the development of both diabetes and other associated neurodegenerative disorders. [28][29][30][31] More experimentation to regulate insulin production and/or provide large systemic dosages of insulin will be required to ascertain whether the OGF-OGFr axis functions to control hyperglycemia and insulin resistance, or whether the insulin pathway has a feedback loop regulating the OGF-OGFr axis. Understanding the timing of dysregulation will enable interventions to be designed to either prevent or ameliorate complications such as dry eye, decreased corneal surface sensitivity, and delayed epithelialization.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on insulin resistance in type 2 diabetes have suggested that the dysregulated insulin pathway is involved in the development of both diabetes and other associated neurodegenerative disorders. [28][29][30][31] More experimentation to regulate insulin production and/or provide large systemic dosages of insulin will be required to ascertain whether the OGF-OGFr axis functions to control hyperglycemia and insulin resistance, or whether the insulin pathway has a feedback loop regulating the OGF-OGFr axis. Understanding the timing of dysregulation will enable interventions to be designed to either prevent or ameliorate complications such as dry eye, decreased corneal surface sensitivity, and delayed epithelialization.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, add-on metformin to neo-adjuvant treatment of ErbB2 breast cancer in non-diabetic patients has recently been reported to fail in improving pathologic complete response [ 54 ], indicating perhaps metformin limitation in the non-diabetic breast cancer context. In light of the role of hyperinsulinemia in breast cancer growth and migration [ 55 ], the robust insulin-sensitizing anti-diabetic activity of MEDICA [ 17 , 18 , 20 , 21 ] may translate to improved treatment of ErbB2 breast cancer in both diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…MEDICA compounds simulate LCFA in activating AMP-activated protein kinase (AMPK) (being 20-folds more potent than metformin) [ 17 ] and in suppressing adenylate cyclase [ 19 ]. MEDICA compounds proved potent anti-diabetic efficacy in type II and I diabetic animal models [ 17 , 18 , 20 ], while suppressing diabetes-induced colorectal cancer [ 21 ]. Also, MEDICA treatment has previously been reported by us to suppress triple-negative breast tumor growth and lung metastasis of mice and cells expressing the polyoma middle T antigen (PyMT) driven by the mammary MMTV promoter (MMTV-PyMT) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms of the onset and development of the disease are well studied, diabetes is difficult to manage and correct. According to the statistics of the International Diabetes Federation, the number of people with diabetes is projected to increase to almost 630 million by the middle of the XXI century [2]. Even despite the active struggle with it.…”
Section: Introductionmentioning
confidence: 99%